2023
DOI: 10.2337/dc23-0635
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Closed-Loop Therapy in Adults With Type 1 Diabetes and Above-Target HbA1c: A Real-world Observational Study

Abstract: OBJECTIVE We explored longitudinal changes associated with switching to hybrid closed loop (HCL) insulin delivery systems in adults with type 1 diabetes and elevated HbA1c levels despite the use of intermittently scanned continuous glucose monitoring (isCGM) and insulin pump therapy. RESEARCH DESIGN AND METHODS We undertook a pragmatic, preplanned observational study of participants included in the National Health Service Eng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…20,[25][26][27] A real-world observational study involving 520 adults (median age 40 years) from 31 NHS diabetes clinics in England reported large glycaemic benefits in those who were willing to continue using a hybrid closed-loop system. 28 Participants in this study had higher baseline HbA1c (mean 79 mmol/mol or 9.4%) than those in randomised trials and were all experienced insulin pump users. They were also switched from intermittently scanned (flash) glucose monitoring, meaning that the impact of using real-time CGM and hybrid closed-loop systems may have both contributed to the positive study outcomes.…”
Section: Fundingmentioning
confidence: 70%
See 1 more Smart Citation
“…20,[25][26][27] A real-world observational study involving 520 adults (median age 40 years) from 31 NHS diabetes clinics in England reported large glycaemic benefits in those who were willing to continue using a hybrid closed-loop system. 28 Participants in this study had higher baseline HbA1c (mean 79 mmol/mol or 9.4%) than those in randomised trials and were all experienced insulin pump users. They were also switched from intermittently scanned (flash) glucose monitoring, meaning that the impact of using real-time CGM and hybrid closed-loop systems may have both contributed to the positive study outcomes.…”
Section: Fundingmentioning
confidence: 70%
“…They were also switched from intermittently scanned (flash) glucose monitoring, meaning that the impact of using real-time CGM and hybrid closed-loop systems may have both contributed to the positive study outcomes. 28 These improvements in glucose and patient-reported outcomes were generalisable across the different hybrid closed-loop systems used [including Medtronic 780G (MiniMed, Inc., Minneapolis, MN, USA), Tandem Control IQ (Tandem Diabetes Care, Inc., San Diego, CA, USA) and CamAPS ® FX (CamDiab Ltd, Cambridge, UK)].…”
Section: Fundingmentioning
confidence: 92%
“…NICE’s decision was aided by real world data from a large scale NHS pilot of the technology, funded by NHS England 45. The data showed that in adults and in children the technology led to markedly better glucose control, reduced risk of hypoglycaemia and its long term complications, and improvements in quality of life measures such as the quality of sleep.…”
Section: Uk Leads the Waymentioning
confidence: 99%
“…An NHS England pilot study evaluating real-world implementation of hybrid closed-loop technology included 251 children and 570 adults with type 1 diabetes [41,42]. Of 226 children and young people with complete data at 6 months, HbA 1c was reduced by 0.7 percentage points and time in target glucose range (3.9 to 10.0 mmol/l) increased from 49% to 63%.…”
Section: Real-world Evidence For Closed-loop Systems In Type 1 Diabetesmentioning
confidence: 99%